Intramolecular hydroamination of alkynic sulfonamides catalyzed by a gold–triethynylphosphine complex: Construction of azepine frameworks by 7-exo-dig cyclization - Ito, Hideto; Harada, Tomoya; Ohmiya, Hirohisa; Sawamura, Masaya (Beilstein Journal of Organic Chemistry, 2011)
The gold-catalyzed, seven-membered ring forming, intramolecular hydroamination of alkynic sulfonamides has been investigated. The protocol, with a semihollow-shaped triethynylphosphine as a ligand for gold, allowed the synthesis of a variety of azepine derivatives, which are difficult to access by other methods. Both alkynic sulfoamides with a flexible linear chain and the benzene-fused substrates underwent 7-exo-dig cyclization to afford the nitrogen-containing heterocyclic seven-membered rings, such as tetrahydroazepine and dihydrobenzazepine, in good yields.
Keywords: azepine; cyclization; gold catalyst; hydroamination; triethynylphosphine